Speciation and thermodynamic properties of La(III)-Cl complexes in hydrothermal fluids: A combined molecular dynamics and in situ X-ray absorption spectroscopy study. (1st August 2022) - Guan, Qiushi; Mei, Yuan; Etschmann, Barbara; Louvel, Marion; Testemale, Denis; Spezia, Riccardo; Brugger, Joël
Abstract: Chlorine is the most common ligand in geofluids, and one of the most important complexing agents for rare earth elements. The geometry and thermodynamic properties of La(III)-Cl complexes determined by previous experimental studies show inconsistency especially at temperature over 350 °C. Here, ab initio molecular dynamics (MD) simulations were employed to determine the nature and thermodynamic properties of La(III)-Cl complexes at temperature up to 500 °C and pressure up to 30 kbar. The simulations were ground proofed by in situ X-ray absorption spectroscopy (XAS) results (400 bar, 25 to 500 °C). Both MD and XAS show an increase in the relative stabilities of chloride complexes with increasing temperature. The formation constants of LaCln 3-n (n = 1–3) complexes were calculated using trmodynamic integration method that is within ab initio MD. The calculated formation constants of LaCl 2+ and LaCl2 + at temperatures below 400 °C agree with Migdisov et al.'s (2009) extrapolations from the Helgeson-Kirkham-Flowers (HKF) equation-of-state. We fitted the HKF equation-of-state parameters of LaCln 3-n (n = 1–3) within the Deep Earth Model (DEW, Sverjensky et al., 2014 ) to enable the calculations of the formation constants up to 1200 °C, 60 kbar, based on the previous experimental data and the new results. The predictions confirm the increased stability of chloride complexes with increasing temperature and further underline the effect of pressure on La speciation: while LaCl3 (aq) becomes important in Cl-rich metamorphic and magmatic hydrothermal fluids (T > 350 °C; P < 5kbar) circulating in the upper crust, LaCl 2+ and LaCl2 + appear to be the dominant complexes under higher pressure characteristic of the lower crust or subducting slab environments.